Construção de movimento causado na língua portuguesa - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
This work analyzed the Caused Motion Construction in the Corpus of Portuguese in order to identify the semantic constraints associated with its pattern in Portuguese. To achieve this goal, the research joined the Construction Grammar, understanding language as an inventory of constructions - correspondences of form and function - which is organized in a network of interrelated units. In this way, the theoretical material consisted in Fillmore, Kay and O'Connor (1988), Goldberg (1995, 2006, 2019), Croft (2001), Michaelis (2006), Traugott and Trousdale (2013), Langacker (2008), and others. And, for the methodological development, the Incorporated Mixed Method was adopted, in which different procedures were used for qualitative and quantitative analysis of the data that were collected in the Corpus do Português, totalizing 1,017 (one thousand and seventeen) occurrences from the 19th and 20th centuries. The research was guided to answer the following Research Problem: What restrictions are associated with the Caused Motion Construction in Portuguese? In this sense, as a provisional explanation, it was assumed that the Caused Motion Construction in Portuguese would have the same restrictions as the Caused Motion Construction in English, but as a prototypical trend, which was confirmed during the analysis. Thus, although every expression presents a relationship between cause and movement, causality is not direct in all occurrences, as evidenced by uses with incidental causality. By incidental causality, it is understood a cause, whose interpretation depends on the interlocutors' knowledge of the world and context, that is, it can be an implication from informations in background. Thus, this dissertation seeks to contribute with discussions about Caused Motion Construction and contributes to Portuguese studies.
Caused motion construction in portuguese
Keywords: Gramática; Construção de movimento causado; Português; Grammar; Caused motion construction; Portuguese; LINGUISTICA, LETRAS E ARTES::LETRAS